Quality Assessment in Supportive Care in Head and Neck Cancer - Bonomo, Pierluigi; Paderno, Alberto; Mattavelli, Davide; Zenda, Sadamoto; Cavalieri, Stefano; Bossi, Paolo (Frontiers in Oncology, 2019)
Quality assessment is a key issue in every clinical intervention, to be periodically performed so to measure the adherence to standard and to possibly implement strategies to improve its performance. This topic is rarely discussed for what concerns supportive care; however, it is necessary to verify the quality of the supportive measures as “supportive care makes excellent cancer care possible”, as it is stated by the Multinational Association of Supportive Care in Cancer (MASCC). In this regard, the quality of supportive care in head and neck cancer patients is a crucial topic, both to allow administration of treatments according to planned dose intensity or surgical indications and to maintain or improve patients’ quality of life. This paper aims to provide insight on state of the art supportive care and its future developments for locally advanced and RM HNSCC, with a focus on quality assessment in relation to surgery, RT and systemic therapy.